Treponemal infections : c - World Health Organization; WHO scientific group (Geneva : World Health Organization, 1982)
Reviews scientific knowledge on the treponematoses with the objective of establishing standards for their diagnosis, treatment and control. The opening sections cover epidemiological and clinical aspects of these infections, laboratory diagnostic tests, and the management of patients. The remaining sections offer practical advice on the control of syphilis and the nonvenereal treponematoses.
Keywords: Treponemal infections